Optimal control and forecasting of complex dynamical systems - Grigorenko, Ilya (World Scientific, 2006)
The core of classical economic analysis represented by William Petty and Adam Smith concentrated on the field of development economics. This classical footing of the study of development is different from the neoclassical perspective in two important respects: it focuses on division of labor as the driving force of development, and it emphasizes the role of the market (the "invisible hand") in exploiting productivity gains that are derived from division of labor. However these aspects have received little attention in the body of literature that represents the modern field of development economics - which largely represents the neoclassical application of marginalism. A notable exception is research that utilizes inframarginal analysis of individuals' networking decisions in an attempt to formalize the classical mechanisms that drive division of labor. This book is a first attempt to collect relevant key contributions and is intended for active researchers in the field of development economics